TWINSPAN classification of vegetation from South West aspect of Lower Tanawal, Abbottabad Pakistan - Bibi, Adeela (Brazilian Journal of Science, 2022)
The aim of this research study was to explore the vegetation of Lower Tanawal, Pakistan from South west aspect. The ordination techniques Two-Way Indicator Species Analysis (TWINSPAN), Extended Correspondence Analysis and Canonical Correspondence Analysis were used to classify the data. TWINSPAN classified the 165 species and 24 stands into four plant communities namely Grewia-Dodonaea-Carissa, Melia–Duchesnea–Oxalis, Pinus–Rubus–Cynodon, and Olea–Punica–Rumex community. This study provided information on the Southwest aspect of the Lower Tanawal vegetation, Pakistan.